Procesos y experiencias en las prácticas de terapia ocupacional en comunidad en Argentina - Vinzón, Valentina (2018)
The recent history of the Occupational Therapy (OT) in Latin America shows great concern for socio-community issues that affect occupations and the daily life of individuals and communities. The occupational therapist, acting in society with the demands that it imposes, must promote possibilities of inclusion, emancipation and participation in people’s social life. Thus, the community as a context of participation to achieve a collectively-built state of well-being, and as a fundamental space of practice and visibility of the OT, requires further studies on this discipline. To be able to make a critical contribution to this area, it is fundamental to analyze, from the perspective of the service users and the occupational therapists of community settings, the effects generated by the interventions as perpetuators or transformative elements of the social realities of people and their communities. The present study, qualitative, is positioned in the socio-critical perspective to describe and analyze the processes and experiences of people who participate in OT programs at the community level, in relations to the changes they generate in their daily lives and life projects, and to know how occupational therapists co-produce these practices. To achieve this objectives, we start with a scoping review of the relevant literature to understand from what foundations and methodologies occupational therapists have been developing their practices in community in the last years (2006-2016). In a second stage, and because it is a collaborative research, we worked from three different occupational therapy programs in community settings of the city of Santa Fe and surroundings, in Argentina. Participant observations, interviews with service users and occupational therapists were carried out, as well as an adaptation of the Photovoice methodology. The results show that the OT community practices studied -linked to social and solidarity economy-, constitute a fundamental space of participation for the users, in the construction of conditions for socio-economic autonomy, the creation of links of support, and the projection of a future of possibilities. Also, from the perspective of the occupational therapists, the co-construction processes of these practices and their actual conditions are described.